Benchmarking of software production costs: results and recommendations - Pereira, L. (2018)
This paper intends to provide a deeper understanding about the software production cost in the banking sector through a benchmarking analysis. Furthermore, the paper provides a set of recommendations to assist organizations become more efficient, productive and more competitive. This analysis was performed based on a representative sample in the Portuguese market based on a sample of 21 projects. These projects represent a total of 37.800 hours and a 2.984.000€ budget. The data collection was completed during 2 months, January and February in 2016 through different business research methods namely 15 Interviews to project managers regarding 21 projects and historical data collection. The sample went through a segmentation in two groups due to the dispersion verified among the results between some banks. These two segments were classified as "Classic Retail" - national banks of high dimension, with market recognition and influential in the Portuguese economy - and "Niche Banks"- smaller banks. Briefly, in terms of rates and considering the "Classic Retail" segment, the discrepancy of rates between the two niches is visible, the average rate of Classic Retail is 64.7% above the Niche Banks segment. In regards to productivity, The Classic Retail’s average is about 11h per unit of software produced while for the Niche segment it is about 2.6h.